2018
DOI: 10.1111/rda.13339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding different levels of caffeine in the extender on some biochemical constituents, enzymatic activities and physical characteristics of chilled and frozen ram semen

Abstract: Two experiments were carried out to determine the efficiency of supplementation of ram semen extender with caffeine on chilled storage and frozen capacity of spermatozoa. In the first experiment, eighty ejaculates were collected by an artificial vagina from five adult Barki rams, aged 2-3 years and weighted 45.0 ± 2.0 kg throughout the experimental period (January to February 2017). The ejaculates were pooled and diluted (1:10) with tris-citric egg yolk extender and were split into five groups. Group 1 served … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In other species, CF and PT did not stimulate motility in bull sperm, but modified kinematic parameters after 60 minutes incubation [33]. In ram, buffalo, and human sperm, the addition of CF and PT to cooled or frozenethawed sperm had a positive impact on motility during the first 30 minutes [24,32,38,39]. On the other hand, donkey sperm seems to not response to CF and PT inclusion [8].…”
Section: Discussionmentioning
confidence: 99%
“…In other species, CF and PT did not stimulate motility in bull sperm, but modified kinematic parameters after 60 minutes incubation [33]. In ram, buffalo, and human sperm, the addition of CF and PT to cooled or frozenethawed sperm had a positive impact on motility during the first 30 minutes [24,32,38,39]. On the other hand, donkey sperm seems to not response to CF and PT inclusion [8].…”
Section: Discussionmentioning
confidence: 99%
“…Shukla and Misra (2014) and Spalekova et al (2014) reported that influence of caffeine on motility of spermatozoa may be related to species-specific and/or dose-dependent. Furthermore, Spalekova et al (2014) and Hamid and Ibrahim (2019) in ram, Barakat et al (2015) in bovine and Shukla and Misra (2014) and Chavda et al (2022) in buffalo spermatozoa, recorded a significant improvement in sperm characteristics using caffeine as an additive to semen extender.…”
Section: Characteristics Of Spermatozoamentioning
confidence: 99%
“…Caffeine (1,3,7-trimethylxanthine) is a natural stimulant belonging to the methylxanthine class and has been utilized as a supplement in sperm capacitation medium to enhance progressive motility in IVF schemes. Inclusion of different levels (0.1 -0.4 mM) of caffeine to Tris-glucose-egg yolk extender during liquid storage of ram semen up to 48 h revealed that low (0.1 mM) and medium (0.2 mM) concentrations of caffeine have a positive impact on physical characteristics and enzymatic activity of ram sperm than higher concentrations [39]. Contrariwise, another study reported no effect of 0.1 mM caffeine supplementation in Tris-citric acid extender on progressive motility after 48 h of liquid storage [38].…”
Section: Plant Extractsmentioning
confidence: 99%